PENYULUHAN PENTINGNYA MEDIA SOSIAL DALAM PENINGKATAN PARTISIPASI POLITIK PEMILU 2024 - Komang Junita Widhipratiwi; Nuning Indah Pratiwi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This Thematic Real Work Lecture (KKN) activity report discusses "Counseling on the Importance of Social Media in Increasing Political Participation in the 2024 Election in Sumerta Kauh Village" which is one way to be able to increase the number of political participation in the 2024 election in Sumerta Kauh Village. The KKN program begins with an observation process to Sumerta Kauh Village to see the condition of the village, then the programs are designed sequentially starting with discussions carried out between KKN group members, supervisors, and village administrators. The method used in the KKN program is designed by beginning with observation, preparation, implementation, and evaluation at the end of each work program implemented. This KKN activity can run well and is supported by related parties in Sumerta Kauh Village. KKN activities carried out through counseling have been successfully carried out and can help the public in insight into the importance of political participation in elections.